Barriers and facilitators of the implementation of the application of pelvic floor muscle training in patients with prostate cancer: a scoping review - Lijuan Wang; Yaqin Li; Ziyi Qi; Wei Wang (Frontiers Media S.A., 2023)
BackgroundPatients with prostate cancer (PCa) benefit significantly from pelvic floor exercises, but recent results indicate that these exercises have not been fully promoted in clinical settings. This scoping review aimed to identify the facilitators of and barriers to pelvic floor muscle training (PFMT) in PCa survivors.MethodsA scoping review was conducted in November 2022. Relevant studies were identified from CINAHL, Embase, PubMed, PsycINFO, and Web of Science databases from their inception to 20 November 2022. Data were analyzed and extracted by two formally trained researchers.ResultsA total of 53 studies were included, most of which were randomized controlled trials. The Tailored Implementation for Chronic Diseases (TICD) model framework was used to identify the contents of seven barriers and promotion areas, as well as a series of sub-domains. The most common barriers to implementing pelvic floor muscle training (PFMT) included the following: the lack of a common scheme in guidelines and the measurement of common standardized outcomes, inadequate self-monitoring or feedback from healthcare professionals to improve PFMT compliance, poor patient compliance, and a lack of implementation equipment and financial support. Good treatment effects and easy operation were the facilitators of PFMT.ConclusionThe implementation of PFMT faces several challenges and opportunities that should be understood thoroughly before implementation. In terms of guidelines and clinical practice, more work is needed, and the possibility of PFMT implementation in various hospitals and community health centers or clinics should be considered.